2018
DOI: 10.1021/acs.biomac.8b00252
|View full text |Cite
|
Sign up to set email alerts
|

Different-Length Hydrazone Activated Polymers for Plasmid DNA Condensation and Cellular Transfection

Abstract: The recent advances in genetic engineering demand the development of conceptually new methods to prepare and identify efficient vectors for the intracellular delivery of different nucleotide payloads ranging from short single-stranded oligonucleotides to larger plasmid double-stranded circular DNAs. Although many challenges still have to be overcome, polymers hold great potential for intracellular nucleotide delivery and gene therapy. We here develop and apply the postpolymerization modification of polyhydrazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 86 publications
0
40
0
Order By: Relevance
“…The protein‐binding units were located at the interface of the hydrophilic/hydrophobic domains to minimize the impact on the secondary structure. Peptide synthesis was accomplished by a solid‐phase approach using orthogonal protecting groups (Figure S1 in the Supporting Information) . The key step was the selective cleavage of the methyltrityl (Mtt) groups of the two lysines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein‐binding units were located at the interface of the hydrophilic/hydrophobic domains to minimize the impact on the secondary structure. Peptide synthesis was accomplished by a solid‐phase approach using orthogonal protecting groups (Figure S1 in the Supporting Information) . The key step was the selective cleavage of the methyltrityl (Mtt) groups of the two lysines.…”
Section: Resultsmentioning
confidence: 99%
“…Peptide synthesis was accomplished by a solid-phase approach using orthogonal protecting groups (Figure S1 in the Supporting Information). [50,51] The key step was the selective cleavage of the methyltrityl (Mtt) groups of the two lysines.Mtt removal proceeded in weakly acidic conditions and the reactive alkoxyamines were then coupled" on resin" for the subsequent incorporation of aldehydes or ketones (R 2 , R 3 ). The peptidew as terminatedw ith either af luorophore (TAMRA), the steroid dexamethasone or by simple acetylation (R 1 ,F igure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…The results reported herein highlight the potential of the glycosylationo fp enetratingp eptides to modulatetheir activity. [17][18][19][20][21][22][23][24][25] Interesting penetrating properties were further discovered in different naturala nd artificial structures, such as polyprolines, [26] guanidinyl glycosides, [27,28] b-peptides, [29] peptiden ucleic acids (PNAs), [30] nonpeptidic guanidinylated dendritic structures, [31] self-assembled nanofibers, [32,33] synthetic polymers, [34][35][36][37] supramolecular structures, [38][39][40] and polydisulfides. [14] These studies also showed that oligolysines were less effective than that of the oligoarginines analogues, [15] and triggered the development of synthetic penetrating oligoarginines.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the next generationo ft herapeutics, such as proteins, nucleic acids and antibodies, or their analogues, [1][2][3][4][5][6] has the potentialt or evolutionise chemical biology and medicine. However,t he transport of these large, hydrophilic and labile biomolecules constitutes ag reat challenge in comparison with traditional small-molecule therapies.…”
Section: Introductionmentioning
confidence: 99%